Ail Cultivation an Innovative Practice Blended with paddy-cum-fish culture for more profit - Maity, U.; Rahaman, S.; Jana, A. K.; Mandal, C. K.; Maitra, N. J. (Indian Farming, 2015)
In the Sunderbans the cultivable land is often inundated by brackish water due to breaches in the embankements. Scarcity of irrigation water during rainy season, accentuated by high salinity in the soil during summer and nonavailability of area specific technology makes it impossible to raise second crops in this region. Most of the populations, under this situation is forced to migrate to other places for their livelihoods. The Ail cultivation system conceptualized by the KVK and through training and demonstration given by NAIP, the small and marginal farmers could reap the benefits and make use of the technology.